Communicating Health at Work: Organizational Wellness Programs as Identity Bridges. Issue 3 (4th March 2017) - Dailey, Stephanie L.; Zhu, Yaguang
ABSTRACT: With the growth in workplace health promotion (WHP) initiatives, organizations are asking employees to enact their personal health identities at work. To understand this prominent yet poorly understood phenomenon, we surveyed 204 employees at a company with a WHP program and found that participation in the wellness program mediated personal health and organizational identities. Results fill a gap in communication literature by demonstrating the effect of individual identity enactment on organizational identification and contribute to recent research stressing the relationship between identity and health behaviors. In addition, findings illuminate the role of situated activity in identity negotiation, suggesting that certain activities in organizations, like wellness programs, serve as identity bridges between personal and work-related identity targets.